Impact of demographic and clinical factors on elagolix plus add-back therapy effects on patient-reported nonbleeding symptoms in women with heavy menstrual bleeding and uterine fibroids: a post hoc analysis of data from two clinical trials - James A. Simon, M.D; Elizabeth A. Stewart, M.D; Susan Jewell, Ph.D; Moming Li, Ph.D; Michael C. Snabes, M.D., Ph.D (Elsevier, 2024)
Objective: To investigate the efficacy of elagolix plus add-back therapy (estradiol [1 mg] and norethindrone acetate [0.5 mg] once daily) on patient-reported nonbleeding symptoms and menstrual bleeding associated with uterine fibroids (UFs) across different subpopulations. Design: Post hoc analysis of two phase 3 clinical trials-Elaris UF-1 and UF-2. Setting: A total of 76 (UF-1) and 77 (UF-2) US clinical sites. Patient(s): Women (N = 591) with UFs and heavy menstrual bleeding. Intervention(s): Elagolix (300 mg) twice daily with add-back therapy (the indicated dose for UF-associated heavy menstrual bleeding) vs. placebo for 6 months. Main Outcome Measure(s): "Very much improved" or "much improved" change in nonbleeding symptoms (abdominal/pelvic pain, abdominal/pelvic pressure/cramping, back pain, and abdominal bloating) and menstrual bleeding measured using a Patient Global Impression of Change scale. Improvements were assessed in subpopulations stratified using baseline characteristics (age, race [self-reported], body mass index, and International Federation of Gynecology and Obstetrics fibroid classification). Result(s): Across subpopulations, differences favored elagolix plus add-back therapy (vs. placebo) for most symptoms at month 1 and all symptoms at months 3 as well as 6. In patients with characteristics commonly associated with high disease burden (age >40 years, Black/African American), those treated with elagolix plus add-back therapy reported significantly greater improvements vs. placebo at months 1-6 (P<.05) for all nonbleeding and bleeding symptoms (P≤.05). Conclusion(s): Premenopausal women with heavy menstrual bleeding and UFs receiving elagolix plus add-back therapy experienced significant improvements in nonbleeding as well as bleeding symptoms from months 1-6, regardless of baseline characteristics. Clinical Trial Registration Number: NCT02654054 and NCT02691494.